2012
DOI: 10.1186/1471-2407-12-244
|View full text |Cite
|
Sign up to set email alerts
|

Methylation signature of lymph node metastases in breast cancer patients

Abstract: BackgroundInvasion and metastasis are two important hallmarks of malignant tumors caused by complex genetic and epigenetic alterations. The present study investigated the contribution of aberrant methylation profiles of cancer related genes, APC, BIN1, BMP6, BRCA1, CST6, ESR-b, GSTP1, P14 (ARF), P16 (CDKN2A), P21 (CDKN1A), PTEN, and TIMP3, in the matched axillary lymph node metastasis in comparison to the primary tumor tissue and the adjacent normal tissue from the same breast cancer patients to identify the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 33 publications
(42 reference statements)
3
35
0
Order By: Relevance
“…BMP6 expression in ER-negative breast cancer was obviously lower than that in ER-positive breast cancer. Previous studies have shown that promoter hypermethylation contributes to the downregulation of BMP6 expression in ER-negative breast cancer patients (15,16). Our results were in agreement with a previous observation (7) and moreover, further analysis also revealed a significant association between tumor cell grade and BMP6 expression in tumor tissues.…”
Section: Discussionsupporting
confidence: 82%
“…BMP6 expression in ER-negative breast cancer was obviously lower than that in ER-positive breast cancer. Previous studies have shown that promoter hypermethylation contributes to the downregulation of BMP6 expression in ER-negative breast cancer patients (15,16). Our results were in agreement with a previous observation (7) and moreover, further analysis also revealed a significant association between tumor cell grade and BMP6 expression in tumor tissues.…”
Section: Discussionsupporting
confidence: 82%
“…In recent studies, the simultaneous presence of RASSF1A and APC methylation from PTs to LNMs was detected. 36,51 In 57 patients, we observed very similar DNA methylation levels in all 4 hypermethylated genes (RASSF1A, APC, CXCL12, and ADAM23) in both the LNM and PT tissues. Taking into account the tumor heterogeneity, we hypothesize that there are partially degraded cell populations present in the circulation, originating from detached cancer cells that are not able to survive and form metastases but have different methylation profiles; their fragments could be represented by a portion of cfDNA in the PL.…”
Section: Discussionsupporting
confidence: 54%
“…These indicated that hypermethylation of BMP6 promoter might be involved in breast tumorigenesis and drug resistance. In fact, previous studies also confirmed that aberrant methylation of BMP6 is involved in various cancers including malignant lymphoma, malignant pleural mesothelioma, T-cell leukemia and multiple myeloma (20,21,(25)(26)(27). In the present study, we noted that aberrant methylation of BMP6 promoter was involved in breast cancer cell drug resistance.…”
Section: Discussionmentioning
confidence: 58%